Two toll-like receptors identified in the mantle of Mytilus coruscus are abundant in haemocytes. Issue 90 (July 2019) - Li, Yi-Feng; Liu, Yu-Zhu; Chen, Yan-Wen; Chen, Ke; Batista, Frederico M.; Cardoso, João C.R.; Chen, Yu-Ru; Peng, Li-Hua; Zhang, Ya; Zhu, You-Ting; Liang, Xiao; Power, Deborah M.; et al.
Abstract: Toll-like receptors (TLRs) are a large family of pattern recognition receptors (PRRs) that play a critical role in innate immunity. TLRs are activated when they recognize microbial associated molecular patterns (MAMPs) of bacteria, viruses, or fungus. In the present study, two TLRs were isolated from the mantle of the hard-shelled mussel ( Mytilus coruscus ) and designated McTLR2 and McTLR3 based on their sequence similarity and phylogenetic clustering with Crassostrea gigas, CgiTLR2 and CgiTLR3, respectively. Quantitative RT-PCR analysis demonstrated that McTLR2 and McTLR3 were constitutively expressed in many tissues but at low abundance. Highlights: Two toll-like receptors (McTLR2 and McTLR3) were identified and characterized in Mytilus coruscus. The two TLRs had a widespread tissue distribution. McTLR2 was the most abundant in haemocytes.